2019
DOI: 10.1002/adsc.201801431
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic C(sp3)−H Activation towards α‐methylenation of Ketones using MeOH as 1 C Source Steering Reagent

Abstract: Unprecedented direct access to terminal enones via a-methylenation of aryl ketones to form C=C bond is achieved under visible-light conditions using methanol as one carbon source substrate and solvent as well. The reaction involves Cu@g-C 3 N 4catalysed in situ oxidation of methanol into formaldehyde followed by dehydrative cross aldol type reaction. Various aryl ketones react efficiently with MeOH, producing a,b-unsaturated carbonyl compounds only in 4-8 h at room temperature in excellent yield (84-97%). Oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Thus, chemists use DMA, DMF, and DMSO instead of formaldehyde, but these substitutes are less reactive than the latter. 31 Rai and co-workers 32 reported for the first time the construction of a CC bond by α-methylenation of aryl ketones ( 82 ) using methanol as the C1 source (Scheme 22). The reaction was carried out under visible light conditions with Cu graphitic C 3 N 4 (Cu@g-C 3 N 4 ) as the catalyst without using any oxidant.…”
Section: Photochemical Utilization Of Methanol As C1 Sourcementioning
confidence: 99%
“…Thus, chemists use DMA, DMF, and DMSO instead of formaldehyde, but these substitutes are less reactive than the latter. 31 Rai and co-workers 32 reported for the first time the construction of a CC bond by α-methylenation of aryl ketones ( 82 ) using methanol as the C1 source (Scheme 22). The reaction was carried out under visible light conditions with Cu graphitic C 3 N 4 (Cu@g-C 3 N 4 ) as the catalyst without using any oxidant.…”
Section: Photochemical Utilization Of Methanol As C1 Sourcementioning
confidence: 99%
“…In 2019, Verma et al reported for the first time that Cu@g-C 3 N 4 nanocomposites catalysed the α-methylation of aryl ketones to form C=C double bonds to enones using methanol as a C 1 source under visible-light irradiation (Scheme 11a). [87] This strategy has mild reaction conditions, short reaction times, simple operation, and high yields, and provides a green and efficient route for the synthesis of high value-added α, β-unsaturated carbonyl compounds. Notably, a yield of ~35 % was obtained under dark conditions.…”
Section: C-methylenation and C-methylationmentioning
confidence: 99%
“…Graphitic carbon nitride (g-C 3 N 4 ) is a well-known semiconductor photocatalyst and also an excellent support to stabilize a metal catalyst for heterogeneous catalysis. Moreover, low-cost g-C 3 N 4 -based catalysts are easy to synthesize and separate from the reaction mixtures, rendering the reuse of catalysts convenient. Following our continuing study of green chemistry and photoredox chemistry, we envisioned that the photocatalytic oxidative hydroxylation of aryl boronic acids to phenols could be accessed efficiently by a g-C 3 N 4 -based heterogeneous photoredox system.…”
Section: Introductionmentioning
confidence: 99%